Uterine torsion with placental abruption and fetal death at term pregnancy: A case report and literature review - Sebsibie, Melat (Ethiopian Journal of Reproductive Health, 2023)
Background: Uterine torsion in pregnancy is a rare event that requires urgent recognition and management. Its presentation is non-specific and ranges from asymptomatic to severe life-threatening conditions such as placental abruption with hemorrhagic shock and maternal and fetal death. Here we describe our case and reviewed similar literature on gravid uterine torsion. To our knowledge, this is the first report of term uterine torsion complicated by placental abruption and fetal death in Africa. Case Presentation: A 28 years old Ethiopian woman gravida III, para II, presented at 37 weeks of gestation with acute severe abdominal pain, mild vaginal bleeding, absent fetal movement, and shock. Emergency cesarean section was decided with a presumptive diagnosis of placental abruption with hemorrhagic shock and intrauterine fetal demise. Intraoperatively, it was realized that the placenta and the dead fetus were delivered through an inadvertent posterior lower segment hysterotomy made on 1800 levo-rotated uterine torsion. Then the uterus was restored to its anatomic position and the posterior hysterotomy was closed. Despite medical measures, the uterus became atonic and a hysterectomy was required. The patient had an uneventful postoperative and postpartum course. Conclusion: Even if gravid uterine torsion is uncommon, it should be kept in mind as one of the differentials in pregnancy-related acute abdominal emergencies due to its non-specific nature and dangerous impact. Furthermore, it can be obscured and associated with other obstetric emergencies, especially placental abruption.